DIVERSIFICATION OF THE AGRICULTURE AIMED TO BIOENERGY PRODUCTION - Martin PRČÍK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Long-term target by 2050 set by the European Commission is based on the development of the competitiveness of the economies that efficiently handles with the natural resources and contributes to reducing carbon emissions. Competitiveness can be increased also by diversification. Later it was integrated the concept of green (low carbon) economy into general policy framework at the national policies of the Member States. Diversification orientation into the bioenergy production represents the use of agricultural land for targeted growing of fast-growing plants under specific conditions. The article evaluated varietal conditionality of Populus biomass production based on soil and ecological conditions of southern Slovakia. The research was realized in the vegetation year 2012 (the last year of the first growing cycle) and 2013 (the first year of the second growing cycle) on a research area in the village Kolíňany, Slovakia. Return cut of the trees (at the end of the vegetation in 2012) influenced biomass production the first year of the second growing cycle by all grey poplar varieties. By all varieties the biomass production in the harvest moisture (t ha-1) decreased in the range from 71.5% variety Monviso to 80.9% Pegaso. Production of dry mass (t ha-1) decreased in the range of 80.28 to 81.70% by three varieties -Pegaso, AF-2 and Sirio. The lowest decrease of dry mass has been researched in a variety Monviso (74.85%). All grey poplar varieties exceeded in the first year of the second growing season (a year after re-section) economic yield limit (12 t of dry matter. ha-1.year-1).